Significance of Hepatic Profile and Malondialdehyde as Marker of Lipid Peroxidation in HCV Patients: A Perspective Study from Local Population of Punjab (Medical Forum Monthly, 2024)
Objective: All over the world Hepatitis C virus (HCV) remains to be a main etiological mediator of liver disease. Approximately, 10 million people in Pakistan are diseased with HCV. Pegylated interferon plus ribavirin signifies the gold standard therapy but various side effects may occur.Study Design: Comparative study.Place and Duration of Study: This study was conducted at Jinnah Hospital Lahore from August 2013 to March, 2014.Materials and Methods: Thirty five patients of hepatitis C virus and Twenty three age and sex-matched clinically apparently healthy individuals were eligible for inclusion in the study at Jinnah Hospital Lahore during the year 2013-2014. 1.0 ml blood sample were taken and subjected to centrifuge at 3000-4000 rpm for 10-15 minutes for the separation of serum. All the analytical work was performed at the Institute of molecular biology and biotechnology (IMBB), and Centre for research in molecular medicine (CRiMM), The University of Lahore-Pakistan.Results: The estimation of AST, ALT, ALP, TP and T.Bilirubin were estimated. The AST level in HCV patients was increases (47.88±40.49) as compared to the control persons (31.43±7.31) and statistically significant (0.02<0.05). Total Protein level in HCV patients was (4.20±0.61) and in healthy individuals (6.23±0.51) and statistically significant (0.000<0.05). MDA level in HCV patients was increases remarkably (8.58±1.19) and in control persons (1.47±0.54) and it was statistically significant (0.000<0.05).Conclusion: There is a relationship between oxidative stress and ALP, ALT, AST and Albumin. The results of the present study confirmed a perfect sketch regarding the circulating biochemical markers and lipid peroxidation (MDA) profile between the studied groups i.e., control and HCV patients with interferon induced Hepatitis C virus infection.